Genomic profiling, prognosis, and potential interventional targets in young and old patients with cholangiocarcinoma - Junhua Wang; Yaoting Shi; Jianbo Chen; Juying Liu; Xiaotian Zhao; Jiaohui Pang; Ximin Sun; Yichen Tian; Qiuxiang Ou; Feng Xia; Yunjie Chen (Cancer Biology & Therapy, 2023)
Molecular mechanisms behind potentially inferior prognosis of old cholangiocarcinoma (CCA) patients are unclear. Prevalence of interventional targets and the difference between young and old CCA patients are valuable for promising precision medicine. A total of 188 CCA patients with baseline tumor tissue samples were subgrouped into the young (≤45 years) and old (>45 years) sub-cohorts. Somatic and germline mutation profiles, differentially enriched genetic alterations, and actionable genetic alterations were compared. An external dataset was used for the validation of molecular features and the comparison of overall survival (OS). Compared to young patients, KRAS alterations were more common in old patients (P = .04), while FGFR2 fusions were less frequent (P = .05). TERT promoter mutations were exclusively detected in old patients. The external dataset (N = 392) revealed no significant difference in OS between young and old patients; however, old patient-enriched KRAS (hazard ratio [HR]: 1.96, 95% confidence interval [CI]: 1.37–2.80) and TERT alterations (HR: 2.03, 95% CI: 1.22–3.38) were associated with inferior OS. Approximately 38.3% of patients were identified of actionable oncogenic mutations indicative of a potential response to targeted therapy or immunotherapy. Actionable FGFR2 fusions (P = .01) and BRAFV600E (P = .04) mutations were more frequent in young females than old patients. The enrichment of KRAS/TERT alterations in CCA patients over 45 years resulted in inferior OS. Approximately one-third of CCA patients were eligible for targeted therapy or immunotherapy given the actionable mutations carried, especially young females.